Web-Based Integrated Disaster Information System For Optimizing The Role and Function of The Data and Information Center (PUSDATIN) Badan Penanggulangan Bencana Daerah Kabupaten Sidoarjo - Dini Aprilia Puspitasari; Ade Eviyanti (Procedia of Engineering and Life Science, 2021)
The Data and Information Center (PUSDATIN) is the main facility for disaster management. Integrated data is the main support in determining disaster management policies. The purpose of research is to built an integrated disaster information system to optimize the function of PUSDATIN. The research method used was interviews and data collection. This system was developed using MySQL and Dreamweaver. There are 3 (three) user levels : user, admin and super admin. The result is an integrated disaster information system on web-based that can be accessed by anyone, according to the level of user, users can execute CRUD commands smoothly, data redundancies can be reduced, and optimization of BPBD resources by using PUSDATIN as 1 (one) gate data. The conclusion of this research is this web-based integrated disaster information system running well and has a positive effect on the performance of PUSDATIN as a traffic data center for disasters and fires.